Influência da fotopolimerização e da cor da resina composta na microdureza - Firoozmand, Leily Macedo [UNESP]; Balducci, Ivan [UNESP]; de Araújo, Maria Amélia Máximo [UNESP] (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2009)
Objective: To study the influence of color opacity and light-curing systems (halogen light vs blue LED) on the microhardness of a composite resin. Methods: Esthet-X composite resin (Dentsply), shades A2 and A2-O, was inserted in a stainless steel matrix (5 mm diameter and 2 mm deep) and was light cured for 40 seconds with a halogen light source (XL 3000; 3M/ESPE) or a blue LED (Optilight LD II; Gnatus). Eight groups of 15 specimens each were formed, and were further divided according to the light-curing systems, the exposed area (base and surface), and the opacity of the composite resin, producing 120 specimens. The specimens were next stored in distilled water for 24 hours, embedded in a chemically activated acrylic resin, then subjected to finishing and polishing with sandpaper and felt discs. Microhardness was measured with a Vickers Digital Microhardness meter, with a 50 g load for 30 seconds. The obtained microhardness means were analyzed by ANOVA and Tukey's multiple-comparison test at 5% significance level. Results: The surface microhardness was always greater than the base microhardness, regardless of the light-curing source. The halogen light lamp produced significantly higher composite resin microhardness means than the blue LED (57.61 vs. 42.53 HV) (p<0.05). Statistically significant differences (p<0.05) were obtained between the microhardness means for the different composite opacities; lowest microhardness in depth was produced by the A2-O shade. Conclusion: Composite resin opacity as well as the light-curing system influenced the microhardness of the material.
Influence of light curing and shade on the microhardness of a composite resin